Synthesis and Study of Electro-Optical Properties of Water-Soluble Polyaniline Prepared by Chemical Oxidation - Assem, Humphrey Darkeh; Agyei, Mensah Samuel; Tamakloe, Reuben Yao; Nkum, Robert K.; Singh, Keshaw (European Journal of Applied Sciences, 2024)
Due to its environmental stability and decent levels of conductivity, polyaniline has recently become one of the more promising conducting polymers; nonetheless, the solubility of the conducting polymers is vital for their uses. The solubility of pure polyaniline (PANI) in water is limited. However, in this research, we successfully synthesized water-soluble complexes of PANI by chemically oxidizing aniline in an aqueous solution containing cellulose derivatives such as methylcellulose (MC), hydroxypropyl cellulose (HPC), and hydroxypropyl methylcellulose (HPMC). The synthesis process involved using aniline as the monomer, hydrogen chloride (HCl) as an acidic dopant, ammonium persulphate (APS) as an initiator, and cellulose derivatives as a steric stabilizer. The resulting PANI composites were easily dissolved in deionized water. To create thin films by the spin coating technique, the PANI composite solutions were coated onto ITO glass substrates at different RPM speeds (1000, 2000, and 3000) for 2 minutes. The thickness of the films ranged from 50 nm to 80 nm. Four characterization techniques were employed to study the electro-optical properties of the prepared samples. Fourier Transform Infrared Spectroscopy (FTIR) was employed to confirm the chemical structure of the PANI complexes, which exhibited distinctive peaks at 3460 cm-1. The interaction between PANI and cellulose derivatives was examined using ultraviolet-visible spectroscopy (UV-Vis) in the wavelength range of 200 nm to 700 nm. The absorbance showed a sharp increase and a red shift around 500 nm, which was further supported by extrapolated bandgap values. For electrical conductivity measurements, we employed the Standard Four-Point Probe Method. The observed electrical conductivity followed the order of PANI > HPC > MC > HPMC, with values ranging from to S/cm for the bulk samples. Similar trends were observed for the thin films. XRD characterization confirmed the presence of PANI and cellulose derivative traces, as indicated by distinct peaks at various two theta angles.